Methods of Converting a Complete Drawing, Application in the Image of Objects (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Currently, it is impossible to imagine the work and development of any branch of the national economy, as well as science and technology without drawings. Drawings (projects) are first developed for newly created devices, machines and structures. According to the drawings, their advantages and disadvantages are determined, and changes are made to their design. Only after discussing the drawings (projects) are prototypes made. The engineer must be able to read the drawing in order to understand both the design and operation of the depicted product, as well as to present his technical thoughts using the drawing.